Microbiological Analysis of Lemon Juice Samples Collected from Local Markets in Dhaka City, Bangladesh (Stamford Journal of Microbiology, 2025)
Lemon juices, widely consumed for their nutritional benefits and sensory appeal, may pose significant public health risks when prepared and sold under unhygienic conditions. This study investigated the microbiological quality of lemon juices sold across various locations in Dhaka, Bangladesh, with a focus on identifying potential contamination sources and assessing the prevalence of bacterial pathogens. While formal establishments such as restaurants and cafes generally maintain acceptable hygiene standards, juices sold by roadside vendors, in parks, and at busy marketplaces often lack proper quality control measures. Microbiological analysis revealed the presence of contaminants, including coliforms, faecal coliforms, and pathogenic bacteria such as Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus, largely attributable to factors such as the use of untreated water, inadequate refrigeration, and unhygienic handling practices. The antibiotic susceptibility profiles of five bacterial isolates revealed that Chloramphenicol was the most effective, demonstrating nearly 100% sensitivity with minimal resistance. In contrast, Piperacillin showed the lowest efficacy, with only 60% susceptibility and higher rates of resistance and intermediate responses. These findings highlight the urgent need for stricter enforcement of food safety regulations and public health interventions to reduce the risk of foodborne illnesses associated with the consumption of lemon juice in urban areas. The study underscores the importance of comprehensive monitoring and improved hygiene practices in safeguarding consumer health.Stam. J. Microbiol. 2025;15(1):13-16